Meeting Water Needs in Vietnam : How Engaging Communities Can Help Lead to Viable Projects - Kingdom, Bill; Reddel, Paul (World Bank, Washington, DC, 2012)
In Vietnam the water supply issue is complicated: given the history of a strongly centralized economy, would the private sector be willing or able to respond to new opportunities in water infrastructure. Pilot projects testing a new approach in two Vietnamese towns provide encouragement: allowing communities a voice in determining how water will be delivered and at what cost can lead to viable and politically acceptable solutions. And the local private sector is responding to the new opportunities.